Unsettled pasts : reconceiving the west through women's history - Carter, Sarah, 1954- (University of Calgary Press, 2005)
This collection stems from a recent conference at University of Calgary that included some of the most established names in the field of women's history in the US and Canada, as well as younger scholars, activists in the Aboriginal community and in farm women's organisations, volunteers in historical societies working to preserve women's voices, family and genealogical researchers, film-makers, a poet, a playwright and many others. Designed to generate writing and research about the West through women's eyes, the central goal of the conference was to spark dialogue across boundaries, whether geographic, cultural or disciplinary. The volume is divided into two parts: the first section discusses the role of women in history as community builders and cultural preservationists, and the second section is concerned with gender history in numerous disciplines such as history, education, nursing and communication studies.; This collection highlights the extent to which Western and women's history remains a contested or unsettled terrain and argues that the greatest strength of historical analyses that take sex and gender into account is their ability to complicate and consequently transcend regional myths and frontier legacies that emerged out of imperial and masculine priorities and perspectives.